2014
DOI: 10.1177/2048872614547690
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact on mediumterm mortality of hematological parameters in Acute Coronary Syndromes: added value on top of GRACE risk score

Abstract: Background: Red Cell Distribution Width (RDW) prognostic value in patients with Acute Coronary Syndrome (ACS) has been well validated whereas that of Platelet Distribution Width (PDW) is less well known. Objectives: Investigate the incremental prognostic value, on top of GRACE risk score, of a new variable resulting from the combination of RDW and PDW. Methods: Consecutive patients with ACS. Complete blood count, with RDW and PDW, was obtained. Primary endpoint was one-year all-cause mortality and Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…It was also reported that adding both RDW and PDW to the GRACE Risk Score can enhance the prediction of all causes of mortality in patients with acute coronary syndrome. 15 Adam et al 16 reported that PDW was associated with the severity of carotid artery stenosis as determined by multidetector row computed tomography angiography. This association suggested that PDW may be a marker of early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that adding both RDW and PDW to the GRACE Risk Score can enhance the prediction of all causes of mortality in patients with acute coronary syndrome. 15 Adam et al 16 reported that PDW was associated with the severity of carotid artery stenosis as determined by multidetector row computed tomography angiography. This association suggested that PDW may be a marker of early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that a high RDW at the time of hospital admission in patients with stable coronary artery disease (SCAD) is associated with an enhanced mortality and incidence of ACS within the subsequent year . RDW may also be helpful in evaluation of risk of mortality after ACS . Nabais et al studied 1,796 patients with ACS, and showed that increased RDW is an independent risk factor for 6‐month mortality or MI in patients with ACS .…”
Section: Rdw As a Biomarker In Coronary Artery Diseasementioning
confidence: 99%
“…25 RDW may also be helpful in evaluation of risk of mortality after ACS. 26 Nabais et al studied 1,796 patients with ACS, and showed that increased RDW is an independent risk factor for 6-month mortality or MI in patients with ACS. 27 Poludasu et al studied patients who underwent PCI and showed that an increased RDW was a risk factor for mortality in patients with normal level of hemoglobin at baseline.…”
Section: Rdw As a Biomarker In Coronary Artery Diseasementioning
confidence: 99%
“…RDW represents a variability of sizes of circulating erythrocytes and is combined with the mean corpuscular volume for the differential diagnosis of microcytosis such as thalassemia, iron deficiency, and chronic disease-related anemia [8,9]. Recently, RDW has been extensively investigated as a significant predictor of clinical outcomes for various disorders, such as acute coronary syndrome, malignancy, and infectious diseases [10][11][12].…”
Section: Introductionmentioning
confidence: 99%